2006
DOI: 10.4161/cbt.5.8.2883
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest induced by C75, A fatty acid synthase inhibitor, Was partially modulated by p38 MAPK but not by p53 in human hepatocellular carcinoma

Abstract: C75, a well-known fatty acid synthase (FAS) inhibitor, has been shown to possess potent anti-cancer activity in vitro and in vivo. In this study, we reveal that C75 is a cell cycle arrest inducer and explore the potential mechanisms for this effect in hepatocellular carcinoma (HCC) cell lines with abundant FAS expression: HepG2 and SMMC7721 cells with wt-p53, and Hep3B cells with null p53. The results showed FAS protein expression and basal activity levels were higher in HepG2 cells than in the other two HCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…Seventy-two hours after transfection of cells with siRNA, 1 ACi of 55 mCi/mmol [2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetic acid (GE Healthcare) was added per six wells for 2 h. Cells were washed with PBS, scraped into 2% KOH, and incubated overnight at 80jC to saponify lipids. Sterols were extracted by adding hexanes and spinning for 5 min at 600 Â g. The organic phase containing sterols was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-two hours after transfection of cells with siRNA, 1 ACi of 55 mCi/mmol [2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetic acid (GE Healthcare) was added per six wells for 2 h. Cells were washed with PBS, scraped into 2% KOH, and incubated overnight at 80jC to saponify lipids. Sterols were extracted by adding hexanes and spinning for 5 min at 600 Â g. The organic phase containing sterols was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…31,33,36 Specifically, silencing of FASN using siRNA or inhibition of FASN activity via the small molecule C75 led to decreased HCC cell proliferation and increased apoptosis. Mechanistically, it has been suggested that FASN may regulate the AKT 33 and p38MAPK 36 cascades. However, overexpression of FASN in the liver, either alone or in combination with other putative oncogenes, such as activated N-Ras or c-Met, does not trigger tumor formation in mice.…”
Section: Increased Lipogenesis In Hccmentioning
confidence: 99%
“…Cancer cells, however, synthesize more than 90% of their triacylglycerol de novo, requiring increased FASN expression ( 1 ). The important role of FASN in cancer cell proliferation/survival and its potential oncogenic function have been demonstrated in several previous studies (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%